A Novel Data Transmission Model Using Hybrid Encryption Scheme for Preserving Data Integrity - Riyaz Fathima Abdul; Saravanan Arumugam (Advances in Technology Innovation, 2025)
The objective of the study is to introduce a novel hybrid encryption scheme, combining both symmetric and asymmetric encryptions with a data shuffling mechanism, to enhance data obfuscation and encryption security. The approach uses RSA for asymmetric encryption and ChaCha20-Poly1305 for symmetric encryption. To increase the complexity, an additional phase involves reorganizing the RSA-encrypted data blocks. Furthermore, symmetric key generation using the key derivation function is employed to generate the key for symmetric encryption through an asymmetric private key. Decryption entails reversing these procedures. This model significantly enhances security through an additional shuffling step, measured by performance metrics like encryption and decryption times, throughput rate, and the avalanche effect. The method, despite increasing execution time compared to symmetric models, yields comparable results for asymmetric models and ensures robustness. The proposed method outperforms traditional methods regarding resistance to cryptanalytic attacks, including chosen-plaintext and pattern analysis attacks.